The ultimate Harry Potter and philosophy : Hogwarts for Muggles - Bassham, Gregory, 1959- (Hoboken, N.J. : Wiley, 2010)
"The Ultimate Harry Potter: Hogwarts for Muggles, is a fresh and distinctive report on the great ideas in the series. All the authors of these chapters have had the advantage of thinking through their chosen issues, and writing up their conclusions after the entire Potter storyline was complete, and Rowling had even had her say in public about things that never made it into the pages of the official texts. The philosophers and other top Harry Potter experts gathered together here offer new voices and new perspectives on many of the most important ideas that come up in the books--some of which can be genuinely life changing. Reading this book will be like putting on a Philosophical De-Coder Ring. It will show you vital aspects of the deepest story that lies behind these famous stories"--
Introduction: Harry Potter and the enchantment of philosophy -- The soul in Harry Potter / Scott Sehon -- Sirius Black: man or dog? / Eric Saidel -- Destiny in the wizarding world / Jeremy Pierce -- Choosing love: the redemption of Severus Snape / Catherine Jack Deavel and David Paul Deavel -- Love potion no. 9 3/4 / Gregory Bassham -- Harry Potter, radical feminism, and the power of love / Anne Collins Smith -- Patriotism, house loyalty, and the obligations of belonging / Andrew P. Mills -- Dumbledore's politics / Beth Admiraal and Regan Lance Reitsma -- Dumbledore, Plato, and the lust for power / David Lay Williams and Alan J. Kellner -- Is Dumbledore gay? Who's to say? / Tamar SzaboÌ{u01E5}ndler -- Choices vs. abilities: Dumbledore on self-understanding / Gregory Bassham -- The magic of personal transformation / S. Joel Garver -- Just in your head? J. K. Rowling on separating reality from illusion / John Granger with Gregory Bassham -- A pensieve for your thoughts? Harry Potter and the magic of memory / Amy Kind -- A Hogwarts education: the good, the bad, and the ugly / Gregory Bassham -- The real secret of the phoenix: moral regeneration through death / Charles Taliaferro -- Beyond Godric's Hollow: life after death and the search for meaning / Johnathan L. Walls and Jerry L. Walls -- Why Harry and Socrates decide to die: virtue and the common good / Michael W. Austin.
Includes bibliographical references and index.
Keywords: Rowling, J. K. -- Philosophy; Rowling, J. K. -- Themes, motives; Rowling, J. K. -- Characters; Potter, Harry -- (Fictitious character); Hogwarts School of Witchcraft and Wizardry (Imaginary organization); Philosophy in literature; Children's stories, English -- History and criticism; Fantasy fiction, English -- History and criticism